A facile approach for the development of high mechanical strength 3D neuronal network scaffold based on chitosan and graphite nanoplatelets. (1st November 2021) - Arnaldi, Pietro; Di Lisa, Donatella; Maddalena, Lorenza; Carosio, Federico; Fina, Alberto; Pastorino, Laura; Monticelli, Orietta
Abstract: In this work, novel composite microparticles based on chitosan (CHI) and graphite nanoplatelets (GNP) were developed as 3D scaffolds for neuronal cells. The aim is to improve the scaffold strength while maintaining its ability to sustain cell adhesion and differentiation. An air-assisted jetting technique followed by physical crosslinking is employed to obtain CHI/GNP microparticles. Optical and Field Emission Scanning Electron Microscopy micrographs showed a uniform distribution of GNP within the CHI porous matrix. The presence of GNP turned out to improve the strength of the microparticles while conferring good electrical conductivity and ameliorating their stability in aqueous environment. The morphological and immunocytochemical characterization, combined with a preliminary electrophysiological analysis, evidenced the effectiveness of the developed composite microparticles as a scaffold for neuron growth. These scaffolds could be employed for the development of advanced 3D neuronal in vitro models for networks dynamics analysis and drug screening. Graphical abstract: Unlabelled Image Highlights: A 3D neuronal network scaffold is developed. The scaffold is made of microparticles based on chitosan and GNP. GNP is homogeneously dispersed within the polymer matrix. GNP increases the strength and improves the stability in water of the scaffold. GNP confers electrical conductivity to the scaffold. The scaffold supports the development of complex neuronal networks.